Indigenous reconciliation in contemporary Taiwan
1 online resource.
Keywords: "This book draws attention to the issues of Indigenous justice and reconciliation in Taiwan, exploring how Indigenous actors affirm their rights through explicitly political and legal strategies, but also through subtle forms of justice work in films, language instruction, museums, and handicraft production. Illustrating that there is new hope for real justice in an era in which states and Indigenous peoples seek meaningful forms of reconciliation, this book is an invaluable resource for students and scholars of Taiwan Studies, Indigenous Studies and Social Justice Studies"--